2018
DOI: 10.1021/acsphotonics.8b00776
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Radiative Heat Transfer between Black Phosphorus Sheets via Anisotropic Surface Plasmon Polaritons

Abstract: Black phosphorus (BP), a novel natural two-dimensional layered material with intrinsic in-plane anisotropy, has been attracting significant research attention due to its outstanding electronic and optical properties and tunable bandgaps. Here, an enhancement of near-field radiative heat transfer (NFRHT) arising from a coupling of anisotropic surface plasmon polaritons (SPPs) between two layered BP sheets is demonstrated. The coupling of SPPs along armchair and zigzag directions dominate the NFRHT at near-infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 50 publications
0
59
0
Order By: Relevance
“…Because of their unique plasmon dispersion, the hyperbolic plasmons can propagate in a certain direction with a large density of states and higher filed confinement, leading to applications of spontaneous radiation enhancement, hyperlens, negative index materials, and thermal management . Many of these have been realized in hyperbolic metasurfaces, created by artificial subwavelength structuring from visible to microwave frequency ranges .…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…Because of their unique plasmon dispersion, the hyperbolic plasmons can propagate in a certain direction with a large density of states and higher filed confinement, leading to applications of spontaneous radiation enhancement, hyperlens, negative index materials, and thermal management . Many of these have been realized in hyperbolic metasurfaces, created by artificial subwavelength structuring from visible to microwave frequency ranges .…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…Understanding radiative heat transfer [1][2][3] is essential in many applications ranging from radiative cooling [4][5][6] and thermal diodes [7] to thermal transistors [8][9][10][11] and thermophotovoltaic systems [12][13][14][15][16]. The majority of works investigating radiative heat transfer consider materials that satisfy Lorentz reciprocity [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. On the other hand, it is known that breaking the constraint of reciprocity is necessary in order to reach the thermodynamic limit of thermal radiation harvesting [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…g) Ratio between the NFRHT and black body heat transfer rates as a function of d ; electron density n = 5 × 10 12 cm −2 . (f,g) Adapted with permission . Copyright 2018, American Chemical Society.…”
Section: Thermal Radiation Engineeringmentioning
confidence: 99%
“…The nearfield density of photonic states dramatically increases due to the contribution of these high-k modes in a broad frequency regime. [119] Recently, Ge et al [110] and Zhang et al [118] theoretically investigated the NFRHT between the two suspended sheets of BP, and reported that the radiative heat flux can exceed the Planck's limit by 10 2 to 10 4 times for separation distance between 100 and 10 nm (Figure 6f,g). Liu and Zhang proposed periodic graphene ribbon arrays to induce hyperbolic modes and predicted a giant enhancement of the NFRHT by more than one order of magnitude.…”
Section: Super-planckian Radiative Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation